2015
DOI: 10.1159/000438927
|View full text |Cite
|
Sign up to set email alerts
|

Leuprolide Acetate Inhibits Spinal Cord Inflammatory Response in Experimental Autoimmune Encephalomyelitis by Suppressing NF-κB Activation

Abstract: Objective: Recent findings have shown that gonadotropin-releasing hormone (GnRH) administration in an animal model of multiple sclerosis (experimental autoimmune encephalomyelitis, EAE) improves clinical signs of locomotion. The present study was designed to determine whether the administration of the synthetic analog of GnRH, leuprolide acetate (LA) - besides its effects on clinical signs of locomotion - also has an effect on the activation/expression levels of molecular markers of EAE, namely transcription n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…As previously reported in literature, most of these factors are affected by action of ZA and LA [25,26,27,28,29,30]. In particular, a direct correlation between GM-CSF and MCP-1 decreased levels and cell invasiveness has been demonstrated [25,28].…”
Section: Discussionsupporting
confidence: 57%
“…As previously reported in literature, most of these factors are affected by action of ZA and LA [25,26,27,28,29,30]. In particular, a direct correlation between GM-CSF and MCP-1 decreased levels and cell invasiveness has been demonstrated [25,28].…”
Section: Discussionsupporting
confidence: 57%
“…More evidence has come also from other Japanese authors who showed that GnRH analogs treatment attenuated the expression of IL-8 by reducing TNF-α-induced NF-κB activation [204]. In an interesting study about spinal cord inflammatory response, Guzman-Soto et al, found that GnRH analog—leurolide has an effect on the activation/expression levels transcription nuclear factor NF-κB and the proinflammatory cytokines like TNF-α [205]. Further research about the connections between GnRH analogs and TNF-α pathways is needed (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effects on the nervous system, it has been reported that GnRH and LA have a direct action on the modulation of the function of the immune system. Specifically, it has been described that GnRH and LA treatments significantly reduce the expression of proinflammatory cytokines (Guzmán-Soto et al 2016, Quintanar andGuzmán-Soto 2013). Also, in rats with acute spinal cord injury, it was found that there was a decrease in activated microglia in the spinal cord of animals that received treatment with LA (Díaz- Galindo et al 2015).…”
Section: Discussionmentioning
confidence: 99%